Cartographic representation of the morphometric characteristics of the basins and valleys west of the Sirwan River (Diyala): (Qala Topzan, Bariola, Issayi, Taza Di) as examples - Barkhas, Khalil Mohamed; Mohammed, Aram Hassan (Al-Adab Journal, 2023)
The aim of this study is to demonstrate the capabilities of geographic information systems for remote sensing (GIS @ RS) in the analysis and cartographic representation of the morphological characteristics of river valleys, including the basins and valleys of the study area (Qalatopzan, pariola, Esayi, Taza De) west of Sirwan River (Diyala). , which is located to the south of the Darbandikhan Dam, with an estimated area of (501.8 square kilometers). It is located between latitudes (34,40,45) and (35,04,52) north and longitudes (45,17,33) and (45,34,11) east within the semi-mountainous region. And based on the use of Arcmap @ RS 108 program, and a topographic map and a hydrological map at a scale (1: 25000), and using the elevation model files (DEM 15 and STREM M15) for the study area, as well as using (ERDAS IMAGIN 2014) for mapping And the production of a geographical database of the morphological characteristics of those basins, to benefit from them in the future in water harvesting, which contributes to the revitalization and development of the basin of the study area.The study reached several conclusions of importance, which is that geographic information systems and remote sensing programs have a high capacity in producing a geographical database for water basins and obtaining all morphological, areal and elevation measurements of water basins in the region with high accuracy and speed.According to the results of the morphometric equations for river valleys in the area covered by the study, it appeared that the average value of height and depression for valley basins ranged between (24.7 - 48.1 m), as well as the value of the hypsometric coefficient for those basins is between (8.5% - 34.3%). This means that the age of the sediments is in the stage of maturity of work, settlement and removal, and the value of the sediment shape coefficient in general was between (0.17 - 0.38), which indicates that most of the valleys’ sediment shapes in the region are close to the triangle shape and far from the shape range.